An Investigation of Determinants Global Entrepreneurship: Multi-Country Panel Studies - Riznaldi Akbar (Universitas Pelita Harapan, 2016)
This study examines the validity of governmental supports and policies; and financing for entrepreneurs in the context of global entrepreneurial activities. Our studies are based on the rich datasets of the Global Entrepreneurship Monitor (GEM) database covering 108 countries from 2001 to 2014. In this study, we examine whether countries with more favorable policies and supports towards entrepreneurship and availability of financing for entrepreneurs would result in the higher country’s entrepreneurial activities.We use total early-stage entrepreneurial activity (TEA), a percentage of 18 - 64 year old population who are either a nascent entrepreneur or an owner manager of a new business, as our dependent variable to represent country’s entrepreneurial activities. There are two main explanatory variables used in the study: governmental supports and financing for entrepreneurs. The governmental supports represents the extent to which public policies support entrepreneurship as a relevant economic issue, while financing for entrepreneurs indicates the availability of financial resources for small and medium enterprises (SMEs) including grants and subsidies. We also include three control variables of basic school entrepreneurial education and training; physical and services infrastructure; and cultural and social norms to test the significance of these factors to the country’s entrepreneurial activities.This study adopts panel regression model augmented with control variables. We favor Random Effect model as opposed to Fixed Effect or Pooled OLS model as Hausman and Breusch–Pagan test suggest. Our results suggest that there is no evident that government supports have significant contribution to country’s entrepreneurial activities. In other words, entrepreneurial activities are more flourished in a country that has not set entrepreneurship as relevant economic issues as it might be the case for many emerging countries. The availability of formal financial resources is significant to the country’s entrepreneurships, but with a negative sign. It could be interpreted that in some countries many new start-ups and entrepreneurs seem to have a greater reliance to informal financing of 4Fs (Founders, Family, Friends and Foolhardy investors) instead of formal channels i.e. government grant and subsidies, venture capital or strategic partners. A country with cultural and social norms that encourage citizens to new business activities also has greater number of entrepreneurships. However, we found no evident that entrepreneurial education and training at basic school; and ease access to infrastructure are significantly affecting entrepreneurial activities in a country.